Načini motiviranja učencev pri pouku matematike - Ilc, Katja (Matematika v šoli, 2013)
In the article we first present some theoretical frameworks for learning motivation and subsequently discuss nine different techniques, offering an example for each.
Keywords: geometrijske naloge; learning motivation; mathematical lessons; motivational approaches; nadarjeni učenci; pouk matematike; teaching methods